A comparison of stress levels, coping styles and psychological morbidity between graduate-entry and traditional undergraduate medical students during the first 2 years at a UK medical school. (December 2017) - Zvauya, R.; Oyebode, F.; Day, E.; Thomas, C.; Jones, L.
Abstract Background Stress levels and psychological morbidity are high among undergraduate medical students (UGs), but there is a lack of research into the psychological health of UK graduate-entry medical students (GEs). GEs are likely to experience different (perhaps more severe) stressors and to cope with stress differently. We compared stress levels, psychological morbidity and coping styles in GE versus UG medical students studying at the same UK medical school in the same academic year. A cross-sectional self-rated questionnaire study of all first- and second-year GE and UG medical students was conducted. Perceived stress, psychological morbidity, recent adverse life events, stress-related personality traits and coping styles were assessed using standard questionnaires. Results 75% GEs and 46% UGs responded to the questionnaire. Both groups reported equally high levels, and similar profiles of, perceived stress and psychological morbidity. Levels of recent adverse life events and stress-related personality traits were similar in both groups. Compared to UGs, GEs were more likely to use active coping (p = 0.02) and positive reframing (p = 0.03), but were also more likely to use substances (alcohol and other drugs; p < 0.001) to help them cope. Unlike UGs, second-year GEs showed less perceived stress (p = 0.007) and psychological morbidity (p = 0.006) than first-year GEs although levels of both were still high. Conclusion Our results show that both GE students and their younger UG counterparts on a traditional medical course have similar profiles of stress symptoms. They do, however, cope with stress differently. GEs are more likely to use active problem-focused coping strategies, and they are also more likely to cope by using substances (alcohol or other drugs). GE students need interventions to prevent maladaptive coping styles and encourage adaptive coping that are tailored to their needs. Such interventions should be targeted at first-year students. It is vital that these students develop positive coping skills to benefit them during training and in a future career that is inherently stressful.